2020
DOI: 10.1136/bmjophth-2020-000453
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome measures in presbyopia: a literature review

Abstract: Presbyopia is the age-related loss of near-distance focusing ability. The aim of this study was to identify patient-reported outcome measures (PROMs) used in clinical trials and quality-of-life studies conducted in individuals with presbyopia and to assess their suitability for use in individuals with phakic presbyopia. Literature searches were performed in Medline and Embase up until October 2017. Specific search terms were used to identify presbyopia studies that included a PROM. All clinical trials with PRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 40 publications
0
27
0
1
Order By: Relevance
“…Previous studies of presbyopia treatment using various treatment modalities [3] used arbitrary numerical criteria to determine treatment efficacy because of the absence of standardized criteria. The patient-reported outcome measures have also been used in clinical trials and quality-of-life studies for presbyopia treatment [3,4]. Among them, the Near Activity Visual Questionnaire was identified as the most appropriate for assessing near-vision functioning in presbyopia, although the measure was not validated in a purely phakic presbyopia sample [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of presbyopia treatment using various treatment modalities [3] used arbitrary numerical criteria to determine treatment efficacy because of the absence of standardized criteria. The patient-reported outcome measures have also been used in clinical trials and quality-of-life studies for presbyopia treatment [3,4]. Among them, the Near Activity Visual Questionnaire was identified as the most appropriate for assessing near-vision functioning in presbyopia, although the measure was not validated in a purely phakic presbyopia sample [4].…”
Section: Introductionmentioning
confidence: 99%
“…The patient-reported outcome measures have also been used in clinical trials and quality-of-life studies for presbyopia treatment [3,4]. Among them, the Near Activity Visual Questionnaire was identified as the most appropriate for assessing near-vision functioning in presbyopia, although the measure was not validated in a purely phakic presbyopia sample [4]. Considering recent developments of presbyopia treatments using various modalities [3,[5][6][7][8][9], simple and easily accessible standardized criteria for diagnosis and endpoints of treatment are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Existing clinical assessment tools (such as visual acuity assessment through use of a standardised Snellen chart) lack adequate assessment of the individual experience of presbyopia, highlighting the need for patient-reported outcome (PRO) instruments in this specific population. A recent literature review found there was a paucity of PROs developed for use in phakic presbyopia in line with the Food and Drug Administration (FDA) PRO guidance [ 16 ]. Phakic presbyopia is presbyopia that occurs for an individual who still has a natural lens, as opposed to pseudophakic presbyopia where the individual no longer has a natural lens (such as following surgery).…”
Section: Introductionmentioning
confidence: 99%
“…{Paley [ 17 ]} Instruments such as the Near Activity Visual Questionnaire (NAVQ) [ 18 ], National Eye Institute Visual Function Questionnaire (NEI VFQ-25) [ 19 ], National Eye Institute Refractive Error Quality of Life Instrument-42 (NEI RQL-42) [ 20 ] were among those identified as PRO instruments that assess vision outcomes of presbyopia or similar conditions. The FDA guidance outlines the requirement of evidence of content validity in a given context of use for existing, modified, or newly created PRO instruments used to support claims in approved medical product labelling [ 16 , 21 ]. The NAVQ was the only PRO identified by the literature review as a suitable instrument to assess patient-reported near vision function [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presbyopia is a physiologic inevitability and aging is the primary etiology. With the development of society, the overuse of portable computers and smartphones has become an important cause of presbyopia [3,4]. Geographic and sex factors have also been reported [5,6].…”
Section: Introductionmentioning
confidence: 99%